Sales, Quantity Surcharge, and Consumer Inattention - Clerides, Sofronis; Courty, Pascal (The Review of Economics and Statistics, 2017)
Quantity surcharges occur when retailers carry a product in two sizes and offer a promotion on the small size: the large size then costs more per unit than the small one. When quantity surcharges occur, sales of the large size decline only slightly even though the same quantity can be purchased for less. We document this behavior in two data sets and four product categories. It is consistent with the notion of passive shoppers found in the industrial organization literature and the notion of rational inattention in macroeconomics. We discuss implications for consumer decision making, demand estimation, and firm pricing.